REST from research to practice - Wilde, Erik 1967-.; Pautasso, Cesare; SpringerLink (Online service). (New York Springer, 2011)
oring ways of developing and implementing applications for REST, the Representational State Transfer system architecture conceived along with the World Wide Web, is gaining prominence as a research topic in academia and industry. Edited by two of the leading lights in REST research, this volume features edited and expanded papers from a key workshop at the 2010 World Wide Web conference, as well as further contributions by researchers on the cutting edge of REST development. The chapters aim to build understanding between those engaged in the abstractions of academic research on REST and the many originators and designers of processes claiming to be RESTful. As well as covering the core principles of REST's architectural style, this significant contribution to the literature on Web development examines a number of REST applications that appear to display advantages over its competing WS architecture. Contributors also assess the benefits REST brings to pervasive computing and cast an eye towards the future with a section on open research questions such as deciding on resource granularity, modeling metadata, and handling transactions.
Introduction -- I. Foundations -- 1. The Essence of REST Architectural Style -- 2. REST and Web Services: in Theory and in Practice -- II. Design -- 3. Designing a RESTful Domain Application Protocol -- 4.Designing Hypermedia Engines -- 5. Beyond CRUD -- 6. Quantifying Integration Architectures -- 7. FOREST An Interacting Object Web -- III. Development Frameworks -- 8. Hypermedia-Driven Framework for Scalable and Adaptive Application Sharing -- 9.RESTful Service Development for Resource-constrained Environments -- 10. A REST Framework for Dynamic Client Environments -- 11. From Requirements to a RESTful Web Service Engineering Content Oriented Web Services with REST -- 12. A Framework for Rapid Development of REST Web Services for Integrating Information Systems -- IV. Application Case Studies -- 13. Managing Legacy Telco Datausing RESTful Web Services -- 14. Case Study on the Use of REST Architectural Principles for Scientific Analysis: CAMERA Community Cyberinfrastructure forAdvanced Microbial Ecology Research and Analysis -- 15. Practical REST indata-centric business applications: the case of Cofidis Hispania -- V. REST and Pervasive Computing -- 16. RESTifying Real-World Systems: a Practical Case Studyin RFID -- 17. Leveraging the Web for a Distributed Location-aware Infrastructure for the Real World -- 18. RESTful service architectures for pervasive networking environments -- VI. REST Research -- 19. On Entities in the Web of Data -- 20. A Resource Oriented Multimedia Description Framework -- 21. Metadata Architecture in RESTful Design -- 22. RESTful Services with Lightweight Machine-readable Descriptions and Semantic Annotations -- 23. Towards Distributed Atomic Transactions Over RESTful Services.
Electronic reproduction.
Keywords: Representational State Transfer (Software architecture).; Web services; Software architecture; World Wide Web; Computer network protocols; Electronic books